2017
DOI: 10.1590/0074-02760170045
|View full text |Cite
|
Sign up to set email alerts
|

Histopathology of murine toxoplasmosis under treatment with dialyzable leukocyte extract

Abstract: BACKGROUNDDialyzable leukocyte extracts (DLEs) contain molecules smaller than 10 kDa with biological activity in receptor organisms. Primarily, they participate in the regulation of the Th1 immune response, which is essential for the control of several intracellular infections, such as toxoplasmosis. This disease is associated with congenital infection, encephalitis or systemic infections in immunocompromised individuals. The clinical course of this infection fundamentally depends on a well-regulated immune re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
15
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 25 publications
5
15
0
4
Order By: Relevance
“…La morbilidad analizada en ratones infectados con T. gondii también puede indicar grados de virulencia variables. Las lesiones histopatológicas y la presencia de quistes en diversos órganos, así como la presencia de ADN parasitario dan cuenta de la patogenia de la infección por T. gondii (Costa et al, 2018;Fuentes-Castro et al, 2017). Cuando se observa por histopatología el SNC afectado por la infección con T. gondii, se han descripto lesiones compatibles con meningitis no supurativa y presencia de manguitos perivasculares.…”
Section: Antecedentes De Ensayos En Modelo Murinounclassified
See 1 more Smart Citation
“…La morbilidad analizada en ratones infectados con T. gondii también puede indicar grados de virulencia variables. Las lesiones histopatológicas y la presencia de quistes en diversos órganos, así como la presencia de ADN parasitario dan cuenta de la patogenia de la infección por T. gondii (Costa et al, 2018;Fuentes-Castro et al, 2017). Cuando se observa por histopatología el SNC afectado por la infección con T. gondii, se han descripto lesiones compatibles con meningitis no supurativa y presencia de manguitos perivasculares.…”
Section: Antecedentes De Ensayos En Modelo Murinounclassified
“…En estudios experimentales realizados en ratones Swiss infectados con la cepa ME49 se observaron infiltrados mononucleares perivasculares focales y multifocales y la aparición de quistes 15 dpi (Pereira et al, 2017). La misma cepa en ratones NIH generó infiltración mononuclear perivascular, nódulos gliales y numerosos quistes (Fuentes-Castro et al, 2017).…”
Section: Antecedentes De Ensayos En Modelo Murinounclassified
“…MSCs may not have anti-Toxoplasma activity. The cyst structure itself is an effective mean of immune evasion by which the parasite protects itself from immune system and drugs [5]. Group II, showed considerable rise in the mean Toxoplasma cysts count (p value< 0.05) compared to group IV and I.…”
Section: Discussionmentioning
confidence: 94%
“…Absence of any one of these pro-inflammatory mediators leads to higher mortality during infection due to uncontrolled tachyzoite growth [4]. The brains of infected mice showed evidence of inflammatory infiltration, gliosis together with T. gondii cysts and proinflammatory cytokines [5].…”
Section: Introductionmentioning
confidence: 99%
“…Also, T. gondii tissue cysts in brain tissues of infected control mice were with intact cyst wall without distortion, similar to notifications by Waree et al, [47] . Fuentes-Castro et al, [48] also recorded the presence of inflammatory infiltration and gliosis around T. gondii cysts in chronically infected mice. In our study, the brain tissue of SPF treated group (G3) showed the presence of a moderate number of Toxoplasma tissue cysts with areas of hemorrhage and tissue infiltration.…”
Section: Discussionmentioning
confidence: 98%